Using human rights to improve maternal and neonatal health: history, connections and a proposed practical approach - Sofia Gruskin; Jane Cottingham; Adriane Martin Hilber; Eszter Kismodi; Ornella Lincetto; Mindy Jane Roseman
We describe the historical development of how maternal and neonatal mortality in the developing world came to be seen as a public-health concern, a human rights concern, and ultimately as both, leading to the development of approaches using human rights concepts and methods to advance maternal and neonatal health. We describe the different contributions of the international community, women's health advocates and human rights activists. We briefly present a recent effort, developed by WHO with the Harvard Program on International Health and Human Rights, that applies a human rights framework to reinforce current efforts to reduce maternal and neonatal mortality.